Implementasi Kurikulum Berbasis KKNI Dalam Upaya Penguatan Mutu Lulusan Pada Program Studi PGMI IAIN Curup - Susilawati Susilawati; Jamalludin Rahmat; Agus Riyan Oktori (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The purpose of this study was to find out how the implementation of the Indonesian national qualification framework curriculum in the Madrasah Ibtidaiyah Teacher Education Study Program IAIN Curup was conducted. This type of research is qualitative and the data collection method is interviews and documentation. The research subjects were lecturers and students of PGMI IAIN Curup. Data analysis starts from data reduction, data presentation and drawing conclusions. The results of this study are that the implementation of the Indonesian national qualification framework curriculum has not been optimal due to various factors including; assistance has not been optimal by LPM IAIN Curup as a center for academic quality control, the Semester Learning Plan which is an extension of the KKNI is just a formality, and not all PGMI lecturers understand the KKNI well. To anticipate these things, what needs to be done is that the PGMI Study Program conducts focus group discussions involving study program devices, lecturers and student representatives, LPM makes official standard rules so that all study programs are uniformly applied, comparisons of the KKNI curriculum with similar study programs so that you know orientation and bring up curriculum updates in accordance with the PGMI IAIN Curup Study Program.